Genetic Variation in CYP2R1 and GC Genes Associated With Vitamin D Deficiency Status. (February 2017) - Slater, Nicole A.; Rager, Michelle L.; Havrda, Dawn E.; Harralson, Arthur F.
This cross-sectional study enrolled 180 patients at a private family practice in Virginia. Total serum vitamin D concentrations were obtained weekly from January 30, 2013, through March 30, 2013, in consecutive patients regularly scheduled for laboratory work at the practice. Patients were categorized into 2 groups and analyzed for variant alleles in vitamin D receptor ( VDR ; rs2228570), cytochrome P450 2R1 ( CYP2R1 ; rs10741657), 7-dehydrocholesterol reductase ( DHCR7 ; rs12785878), and group-specific component ( GC ; rs2282679) to determine whether variants of those alleles influenced total serum 25(OH)D concentrations. One-hundred and eighty patients were enrolled, with 40 (22%) being sufficient, 25-hydroxy vitamin D level 25(OH)D ≥ 30 ng/mL, and 140 (78%) being insufficient, 25(OH)D < 30 ng/mL. Of the 4 genes, 2 genes, CYP2R1 (rs10741657) and GC (rs2282679), demonstrated a significant association related to vitamin D status. Subjects with 1 or more variant alleles at rs10741657 were almost 3.7 (odds ratio [OR] 3.67; 95% confidence interval [CI]: 1.35-9.99) times more likely be insufficient in vitamin D and subjects with 1 or more variant alleles at rs2282679 were about half (OR 0.42; 95% CI: 0.18-0.93) as likely to be insufficient in vitamin D. Allelic variations in CYP2R1 (rs10741657) and GC (rs2282679) affect vitamin D levels, but variant alleles on VDR (rs2228570) and DHCR7 (rs12785878) were not correlated with vitamin D deficiency, 25(OH)D < 30 ng/mL.